2013
DOI: 10.5152/balkanmedj.2013.8571
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar or Unipolar Hemiarthroplasty after Femoral Neck Fracture in the Geriatric Population

Abstract: Background: The choice of prosthesis in hemiarthroplasty is controversial for geriatric patients after femoral neck fracture. We hypothesised that selection criteria for unipolar or bipolar prostheses could be constructed based on factors affecting mortality. Aims:The aims of this retrospective study were: (1) to determine the factors affecting mortality of femoral neck fracture patients ≥65 years of age; (2) to compare patient mortality rates, radiological findings, and functional outcomes according to prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…However, the choice of prosthesis is remain controversial; some authors advocate the cemented prosthesis, whereas others prefer the cementless prosthesis [7][8][9][10]. Internal diseases, cardiovascular diseases in particular, which are observed in advanced age groups, indicate that early mobilization is of utmost importance in terms of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the choice of prosthesis is remain controversial; some authors advocate the cemented prosthesis, whereas others prefer the cementless prosthesis [7][8][9][10]. Internal diseases, cardiovascular diseases in particular, which are observed in advanced age groups, indicate that early mobilization is of utmost importance in terms of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hemiarthroplasty, which allows rapid rehabilitation, is performed as an alternative to osteosynthesis in elderly patients with femoral neck fractures [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 mm/year 12 . In a study Ayhan et al suggested that although the bipolar head movement was preserved in inactive patients, they suppose that this conferred no advantage to these patients, who could hardly walk 13 . Furthermore Calder et al recommend that a unipolar prosthesis may give better short-term results in octogenarians 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracapsular neck of femur fracture is a common injury in the elderly and the incidence of this fracture is increasing year after year due to improvement of life expectancy. (1,2) Although the treatment options are still controversial, joint replacement has shown that it has achieved early return to a satisfactory functional status. (3) Among joint replacement options, hemiarthroplasty has less operative time and less blood loss.…”
Section: Introductionmentioning
confidence: 99%